IMPROVEMENT OF BILINGUISM IN INJECTABLE INJECTORS AT HIGHER TRAINING INSTITUTIONS - QIZI, DANIYAROVA SITORA QULMAT (Confrencea, 2024)
The vibrant tapestry of global interconnectedness has ushered in an era of linguistic diversity and cultural exchange, underscoring the profound significance of foreign language acquisition among students in today's educational landscape